Experimental Investigation of AWJ Slicing of Single Crystal Silicon Using Fuzzy Grey Relational Analysis (FGRA) - Sundararaj, Oliver Nesa Raj; Sethuramalingam, Prabhu (SILICON, 2022)
This investigative research work studies the effect of slicing parameters like water jet pressure (P), abrasive flow rate (AFR) and stand-off distance (SOD) on the surface roughness (Ra), material removal rate (MRR), flatness (F) and inclination angle (θ) accomplished under Taguchi’s L9 orthogonal array. Three different abrasive grain sizes of 80,120 and 120 with CNT mesh size garnet are used to slice the single crystal silicon by abrasive water jet machining (AWJM).To optimize the multiresponse characteristics of the sliced surface, a modified grey- based fuzzy algorithm is generated by an amalgamation of Grey relational analysis and Fuzzy logic to determine the most preferred process responses. The highest Grey–fuzzy reasoning grade (GFRG) is obtained for the water pressure of 300MPa, abrasive flow rate of 0.44kg/min and the standoff distance of 4 mm which are identified as the optimal parameter levels for the slicing process conducted by the 120 mesh garnet with CNT. To find the significance of these parameters on the multiple high quality characteristics, analysis of variance (ANOVA) is carried out and it is seen that the stand-off distance has a significant contribution on GFRG followed by the abrasive flow rate and water pressure. In addition, the sliced surfaces are examined by 3 D optical profilometer, scanning electron microscope (SEM) and atomic force microscope (AFM). These analyses are carried out to understand the surface morphology of the sliced silicon samples. Raman spectroscopy analysis is performed to study the crystallization characteristics of the sliced samples. The surface irregularity and its influence on the optical properties of the sliced samples for different abrasive particle sizes are studied using a UV-VIS spectrophotometer.